Coccolith determination of ODP Site 184-1143 - Xiaobo Jin (PANGAEA, 2020)
Ocean Drilling Program (ODP) Site 1143 is located in the southern South China Sea (113.285° E, 9.362° N) at a water depth of 2,772 m. Age model is based on the benthic foraminifer δ18O stratigraphy (Tian et al., 2002; https://doi.org/10.1594/PANGAEA.700904). A total of 128 samples are collected ranging from 0 to 100 m of composite depth below the seafloor, corresponding to ages from 0 to ~2.1 Ma for coccolith analysis. For each sample, approximately 150 mg of dry sediments are suspended in 200 mL deionized water, and 0.375 mL of the suspension is micropipetted and evenly dropped onto a coverslip. After drying on a hot plate at 35 °C, the slides are sealed with Norland Optimal Adhesive (No. 74). For coccolith abundance and flux analysis. The slides are observed under a polarized light microscope (Leica DM6000B) at exttimes1,000 magnification. In each sample, a total of ~50 to >500 Noelaerhabdaceae coccoliths are counted in 6 one-quarter fields of view (FOVs). Coccolith abundance (CA, coccoliths g-1) can be calculated as: CA=(NC/n) exttimes(A/(f exttimesW)), where Nc/n is the average number of coccolith counted per FOV, A is the area of a coverslip, f is the area of an FOV, and W is the dry sediment weight. Coccolith flux (export production) (CF) (cm-2 kyr-1) can be calculated as: CF=CA exttimesLSR exttimesDBD, where linear sedimentation rate (LSR, cm kyr-1) is resolved by the age model at Site 1143; DBD is dry bulk density (g cm-3). For coccolith morphological analysis. The slides are photographed under circular-polarized light (Zeiss Axio light microscope) using an 8-bit black-white digital camera (Mrc5) at exttimes1,250 magnification with a resolution of 0.088 μm pixel-1. For each sample, approximately 150–250 Noelaerhabdaceae coccoliths are measured for coccolith thickness, coccolith area, and coccolith length using Image J software. Coccolith thickness is determined based its brightness under the light microscope. Coccolith mass (CM, pg) can be calculated as: CM=2.7 exttimesAC exttimesCT, where AC is coccolith area (μm2) and calcite density is 2.7 pg μm-3. Finally, Noelaerhabdaceae coccolith calcite export production or coccolith mass accumulation rate (MAR, g CaCO3 m-2 yr-1) can be calculated based on CF and average CM: MAR=CF exttimesCM.